2018
DOI: 10.18488/journal.1.2018.811.1077.1087
|View full text |Cite
|
Sign up to set email alerts
|

Students Readiness and Motivation to Use Mobile Phone for Learning English at Higher Learning Institution

Abstract: The rapid growth on ICT have reshaped our live today, and nowadays' university students in Higher Learning Institutions have an immense use of mobile phones, iPads and other portable devices. Mobile learning or m-Learning focuses on the mobility of the learner while interacting with portable technologies. The use of mobile learning among university students is seen as an alternative to increase their interest and motivation on learning the academic programmes at Higher Learning Institution. The m-learners use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…On the other hand, our study also found that motivation has a significant correlation with the enhanced readiness of VR practitioners. The study results also agreed with many recent articles that illustrated a direct correlation between motivation and learner readiness in participating in e‐learning (Yılmaz, 2017), m‐learning (Mizad, Yusoff, Sayadi, Latif, & Sukiman, 2018), as well as other training and development approaches (Kim, Park, & Kang, 2019). Nevertheless, not much study has been conducted to determine the relationship between motivation and enhanced readiness for VR training.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, our study also found that motivation has a significant correlation with the enhanced readiness of VR practitioners. The study results also agreed with many recent articles that illustrated a direct correlation between motivation and learner readiness in participating in e‐learning (Yılmaz, 2017), m‐learning (Mizad, Yusoff, Sayadi, Latif, & Sukiman, 2018), as well as other training and development approaches (Kim, Park, & Kang, 2019). Nevertheless, not much study has been conducted to determine the relationship between motivation and enhanced readiness for VR training.…”
Section: Discussionsupporting
confidence: 91%
“…The results from the semi-structured interview reported that readiness was defined by the themes availability, usability and positivity of the use of smartphone for learning language skills purpose. These findings were supported by the studies [17], [18], [20], [21], [23] where learners' readiness reported as high level.…”
Section: 1supporting
confidence: 72%
“…Similarly, in Malaysia, a quantitative study carried out among ter-tiary level learners to explore the readiness of using mobile devices in higher education at a public university. The study reported that learners had a significant level of readiness categorizing as basic readiness, skills readiness, psychological readiness, and budget readiness [23].…”
Section: Learners' Readiness To Use a Smartphone In Global Contextsmentioning
confidence: 99%
“…Previously, research on parenting practices and styles revealed that male and female parents showed a significant different in raising their children; however, this study believed that due to the negative implications of rapid development, globalisation, modernisation and other constraints faced by today's parents, both need to undertake almost similar responsibility towards their children, especially in terms of the child protection and privacy. Although the role theory can explain the differences between fathers and mothers; however, through gender socialisation, male and female parents are continuously learning the social expectations associated with one's sex (Garcia & T. de Guzman, 2017;Mizad, et al 2018).…”
Section: Discussionmentioning
confidence: 99%